MEASURING DETERMINANTS OF MSME TAXPAYER COMPLIANCE - Santoso, Aprih (PT Larva Wijaya Penerbit, 2022)
The purpose of this study is to analyze the effect of taxpayer awareness, modern tax administration system, tax amnesty, taxpayer knowledge, tax rates, tax sanctions and service quality on MSME taxpayer compliance in Semarang City. This research was conducted using quantitative research methods and analyzed using multiple regression analysis. The data used are primary data obtained through filling out questionnaires. The population of this study is all MSME taxpayers in the city of Semarang. The sample used was 197 respondents using the Quota Sampling technique. The results of this study indicate that the variables of the influence of taxpayer awareness, modern tax administration systems, tax amnesty, taxpayer knowledge, tax rates, tax sanctions and service quality have a positive and significant effect on MSME taxpayer compliance in Semarang City. The adjusted R square value in the regression model is 0.743, which means that 74.3% of the taxpayer compliance variable can be explained by the variables influencing taxpayer awareness, modern tax administration systems, tax amnesty, taxpayer knowledge, tax rates, tax sanctions and service quality. tax officers while the remaining 25.7% is explained by other variables outside this study, such as: location, social norms.